Factors Related to Depressive Symptoms among Adolescent Amphetamine Users - Uthis, Penpaktr; Suktrakul, Sunisa; Sonlar, Kongjak; Sawangpon, Mali (Journal of Health Science of Thailand, 2018)
Depressive symptoms are a common problem among adolescent amphetamine users. However, there is a lack of information in Thai adolescent who take amphetamine. The objectives of this cross-sectional correlation research design were to study situation of and factors related to depressive symptoms among adolescent amphetamine users. The subjects of 405 male and female adolescent, aged of 12-24 years old, were amphetamine users who received treatment at 4 Thanyalak hospitals under the Department of Medical Services. The 8 study instruments had Cronbach alpha coefficient reliability between 0.73 -0.97. Data were analyzed using descriptive statistics, Pearson product-moment correlation coefficient, and Odds Ratio. Findings: The majority of subjects had depressive symptoms in mild to severe level (53.6%). Personal and substance related factors to depressive symptoms were poor health conditions, early-onset of methamphetamine use, history of alcohol consumption, severity of amphetamine use, the current use, high doses and more frequent use, and health problems as consequences of amphetamine use (OR = 2.02, 1.65, 1.63, 2.56, 1.77, 2.52, 2.42 and 2.19, respectively; p<0.05). Psychological factors that correlated to depressive symptoms were self-esteem, problem-focus coping using self-com-petencies, avoidance coping, family hardiness, social support from peers, and resilience to amphetamine relapse (r =-0.36, -0.23, 0.22, -0.22, -0.17, and -0.21, respectively; p<0.05). In order to provide appropriate care, all adolescent amphetamine users who get access to treatment should be screened for depressive symptoms. In addition, all factors that had been found to be related to depressive symptoms should be taking into account.